A buffer-aware dynamic UAV trajectory design for data collection in resource-constrained IoT frameworks. (May 2022) - Mazumdar, Nabajyoti; Roy, Saugata; Nag, Amitava; Singh, Jyoti Prakash
Abstract: The emergence of unmanned aerial vehicle (UAV)-enabled technology in the Internet of Things (IoT) era leads to a significant reduction in data collection delays when accumulating sensory data from ground IoT nodes (INs). As a flying data collector, the UAV hovers at a limited number of Access Points (APs) to collect data, outperforming ground data collectors in terms of transmission energy consumption, data delivery reliability, and timeliness. However, the INs have a finite amount of buffer capacity to store the data that must be collected before they overflow. As a result, the data gathering route for UAVs should be adaptable to INs' buffer deadline in order to minimize data loss. In this paper, a buffer-aware dynamic UAV trajectory design protocol is proposed for data collection from resource-constrained INs. A distributed AP nomination strategy is proposed in order to reduce UAV hovering latency. Furthermore, using machine learning approaches, a modified ant colony optimization algorithm is constructed to minimize the data loss penalty due to buffer overflow. Finally, the performance of the proposed scheme is evaluated against several state-of-the-art protocols with regards to parameters such as data loss penalty, packet delivery ratio, and network lifetime. Graphical abstract: Highlights: The UAV Access points selected ensure one-hop connectivity with IoT nodes. To reduce the data collection latency, a minimal set of Access points are nominated. A modified ACO algorithm is used to create a dynamic UAV trajectory.